TRADISI LEBARAN KETUPAT DI KAMPUNG JAWA KOTA TOMOHON - Zulkarnaen Me’akhir Yanus Putra Hulu (Universitas Sam Ratulangi, 2023)
Kampung Jawa is one of the villages in Tomohon City which was founded in 1875 by Muslim freedom fighters from Serang City, Banten Province. The fighters were interned by the Dutch to Minahasa because they were considered dangerous. This village they named Kampung Jawa to commemorate the land of their ancestors Java. But by the inhabitants of Tomohon it is called